2019
DOI: 10.3758/s13414-019-01784-7
|View full text |Cite
|
Sign up to set email alerts
|

What first drives visual attention during the recognition of object-directed actions? The role of kinematics and goal information

Abstract: The recognition of others' object-directed actions is known to involve the decoding of both the visual kinematics of the action and the action goal. Yet whether action recognition is first guided by the processing of visual kinematics or by a prediction about the goal of the actor remains debated. In order to provide experimental evidence to this issue, the present study aimed at investigating whether visual attention would be preferentially captured by visual kinematics or by action goal information when proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 71 publications
1
4
0
Order By: Relevance
“…In this sense, our results align with multiple studies that have shown how participants may concentrate on the action's goal component more than on its manipulation component (e.g., Massen & Prinz, 2007;Osiurak & Badets, 2014). These goalrelated patterns have also been traced in observational investigations where observers looked at an actor using an object (e.g., Decroix & Kalénine, 2019;Naish, Reader, Houston-Price, Bremner, & Holmes, 2013;Nicholson, Roser, & Bach, 2017;van Elk, van Schie, & Bekkering, 2008). Such studies investigated the action's goal component regarding objects' functional AOIs, thus implicitly referring to the semantic/technical knowledge retrievable by looking at objects.…”
Section: Discussionsupporting
confidence: 89%
“…In this sense, our results align with multiple studies that have shown how participants may concentrate on the action's goal component more than on its manipulation component (e.g., Massen & Prinz, 2007;Osiurak & Badets, 2014). These goalrelated patterns have also been traced in observational investigations where observers looked at an actor using an object (e.g., Decroix & Kalénine, 2019;Naish, Reader, Houston-Price, Bremner, & Holmes, 2013;Nicholson, Roser, & Bach, 2017;van Elk, van Schie, & Bekkering, 2008). Such studies investigated the action's goal component regarding objects' functional AOIs, thus implicitly referring to the semantic/technical knowledge retrievable by looking at objects.…”
Section: Discussionsupporting
confidence: 89%
“…The rather low performances in the task most likely reflect the important working memory load induced by the response procedure. Indeed, our previous experiments with similar tasks and design revealed high-level of accuracy in performing perceptual judgements 18,41 . Similarly, perceptual judgements were rather high (90%) in the pre-test (cf.…”
Section: Resultsmentioning
confidence: 77%
“…Many experimental psychology and cognitive neuroscience studies have tackled this question by designing experiments in which each component is manipulated independently. For instance, participants can have to "imitate" a model performing a tool-use action while either the motor action or the mechanical action is congruent with the participant's tool-use action [47] or to judge the appropriateness of a model's tool-use action while the motor action is correct versus incorrect and/or the mechanical action is correct versus incorrect [48][49][50][51]. The conclusions drawn from these studies are that (i.)…”
Section: Goal Versus Meansmentioning
confidence: 99%